Assessment of combustion rates of coal chars for oxy-combustion applications. (15th February 2019) - Senneca, O.; Vorobiev, N.; Wütscher, A.; Cerciello, F.; Heuer, S.; Wedler, C.; Span, R.; Schiemann, M.; Muhler, M.; Scherer, V.
Graphical abstract: Abstract: A drop tube reactor with high heating rates typical of pulverized boilers (>10 4 K/s) has been used to carry out experiments with coal in different atmospheres: N2, CO2, O2 /N2 and O2 /CO2 . The reactor wall temperature was set at 1573 K and the particles' residence time was kept below 130 ms. In O2 /N2 and O2 /CO2 atmospheres coal pyrolysis was complete and additional char conversion occurred. The degree of char conversion increased with oxygen concentration values but was further enhanced by the presence of carbon dioxide, suggesting a positive contribution of CO2 to the overall rate of conversion. Chemico-physical and structural analysis of chars revealed internal burning under regime II conditions and highlighted that the presence of CO2 favors the formation of lactones in the chars. In N2 and CO2 atmospheres the pyrolysis stage was completed, but char conversion was negligible. The combustion stage of the N2 and CO2 chars was investigated in a second stage by thermogravimetric (TG) analysis (in regime I conditions) and in a flat flame burner (in regime II conditions) to separate atmospheric effects on char formation from those on char combustion. In TG, the CO2 chars resulted to be less reactive then the N2 chars, but in the flat flame burner, the experimental rate of carbon conversion of the N2 char and the CO2 char were similar. The TG results were worked out to estimate the intrinsic kinetics of the N2 and CO2 chars towards oxygen, carbon dioxide and O2 /CO2 mixtures. Kinetic rate expressions were extrapolated to regime II conditions after consideration of mass transfer limitations. Notably, the kinetic model developed for the CO2 -char matched the observed rate of char (oxy-) combustion well, whereas the kinetic model of the N2 -char overpredicted the reaction rate.